Analysis of the Effect of the Head of Room's Leadership Style and Nurse's Hand Hygiene Compliance on the Prevention of Nosocomial Infections in Hospital - Agustin, Silvi; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the influence of the leadership style of the head of the room and nurses' handwashing compliance on the prevention of nosocomial infections in hospitals—quantitative research with a survey approach involving 123 respondents with a proportional random sampling method. Data acquisition was done using a questionnaire instrument to measure the perception of leadership style, compliance, and prevention of nosocomial infections, and it was analyzed using a correlation test. The results of the T-test showed a Sig. Value of 0.001 <0.05, and the F test showed a Sig. Value of 0.002 <0.05 with a calculated F value of 41.437 indicating a significant influence between the leadership style of the head of the room and handwashing compliance on the prevention of nosocomial infections. This study concludes that the leadership style of the head of the room and nurses' hand hygiene compliance plays an important role in efforts to prevent nosocomial infections.